Graffiti as a Learning Medium for Fine Arts in Elementary Schools - Witjaksono, M Dimas Yudi; Masunah, Juju; Karyono, Tri; Prawira, Nanang Ganda; Soetedja, Zakarias S. (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study aims to analyze graffiti as a medium for learning fine arts in elementary schools, particularly in exploring students' learning experiences in depth. The study used a qualitative approach with a phenomenological method conducted at Beringin Raya 1 Elementary School, Kemiling District, Bandar Lampung City from June to August 2025. Participants were selected through purposive sampling techniques from third-grade students who showed a high interest in fine arts. Data were collected through participant observation, semi-structured interviews, and documentation of works, then analyzed using a six-stage thematic analysis, namely data familiarization, initial coding, theme search, theme review, theme definition, and report writing. The results of the study revealed three main themes, namely: (1) expression of identity through personal symbols, (2) freedom to experiment with color and shape, and (3) positive and meaningful learning experiences. These three themes show that graffiti, when integrated into formal learning with an approach that frees expression, is able to activate the core components of creativity while fostering students' intrinsic motivation. This study concludes that graffiti has great potential as a medium for learning fine arts that is contextual and relevant to students' contemporary visual culture, and recommends its more explicit integration into the elementary school fine arts curriculum.